2017
DOI: 10.1039/c6ra26305d
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-free synthesis of 5-(aryl/alkyl)amino-1,2,4-triazines and α-arylamino-2,2′-bipyridines with greener prospects

Abstract: A convenient approach towards 5-(aryl/alkyl)amino-1,2,4-triazines and α-arylamino-2,2′-bipyridines was developed following ipso-substitution of a cyano-group by amino groups and, finally, aza-Diels-Alder reaction with 1-morpholynocyclopentene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…The substitution of cyano group in 1,2,4-triazines under the action of aromatic and aliphatic amines in heat was also reported by our group [22]. Based on the experimental data it was demonstrated that the residues of higher alcohols, such as decanol and tetradecanol, could be also successfully introduced into 1,2,4-triazines under the solvent-free conditions during the heating for 10 h at 150 °C.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…The substitution of cyano group in 1,2,4-triazines under the action of aromatic and aliphatic amines in heat was also reported by our group [22]. Based on the experimental data it was demonstrated that the residues of higher alcohols, such as decanol and tetradecanol, could be also successfully introduced into 1,2,4-triazines under the solvent-free conditions during the heating for 10 h at 150 °C.…”
Section: Resultsmentioning
confidence: 57%
“…Замещение циа-ногруппы в составе 1,2,4-триазинов в условиях отсутствия растворителя ранее было нами показано на приме-ре ароматических и алифатических аминов [22]. Эксперименты показали, что аналогичным образом возможно введение остатков высших спиртов, что продемонстрировано нами на при-мере деканола и тетрадеканола.…”
Section: In Russianunclassified
“…5‐Cyano‐1,2,4‐triazines ( 1 ) are easily accessible and could be obtained using previously reported approaches via S N H reactions of 1,2,4‐triazine‐4‐oxides, and the starting 1,2,4‐triazines 1 and their derivatives could be prepared as described earlier . The ipso ‐substitution of the 5‐cyano group in 1,2,4‐triazines is widely reported for various nucleophiles, for instance amines, alcohols ,[18][13] lithium carboranes, etc.…”
Section: Resultsmentioning
confidence: 99%
“…Нуклеофилами могут выступать амины [1][2][3][4], спирты [3] и СН-активные соединения [5]. В принципе, анилины также вступают в данную реакцию, но делают это весьма неохотно, лишь после длительного нагрева [6].…”
Section: In Russianunclassified
“…Amines [1][2][3][4], alcohols [3] and CH-active compounds [5] can act as nucleophiles. In principle, anilines also enter into this reac-tion, but do so very reluctantly only aft er prolonged heating [6].…”
Section: 24-mentioning
confidence: 99%